Marine biology life in the tropical sea - Cousteau, Jan-Michel; Murphy, Richard C.; Living Design Corporation ([s.l.] : distributed by BFA Educational Media, 1900)
A documentary film by Cousteau about the many marine animal groups living in tropical waters, largely with coral reefs. Emphasizes the delicate balance of these environment.
1 videocassette (VHS) (12 mins.)
Intended audience : Intermidiate, Junior high
Film edited and music composed by Anthony J. Miller ; photography, Ron Taylor
Keywords: Marine biology -- Tropics; Coral reef biology -- Tropics